The oil and ozokerite mine in Boryslav and historical monuments of petroleum and salt industries in the vicinity of Boryslav (Ukrainian Fore-Carpathian region) - Radwański, Andrzej B. (Geotourism/Geoturystyka, 2025)
The Boryslav region was one of the world largest petroleum basins, discovered in the second half of the 19th century. Situated southwest from Drohobych, it includes several localities: Boryslav – Tustanovychi – Mraznytsa – Banya Kotyvska with their rich and long history of brine and salt industry dating back to the 12th century. Rapid development of mining activity has commenced with the implementation of the new, Canadian method of drilling for oil by the Canadian MacGarvey Company. The decisive date in the activity of the MacGarvey Company was 1893 when exploration drilling for oil commenced in Boryslav and then, in 1895, in Tustanovychi. Discovery of an oilfield in Boryslav was the beginning of the “golden age” of the oil industry in the Fore-Carpathian region and many people amassed fortunes. From the geological point of view, the Boryslav region covers the three Carpathian structural units: Skyba (Skole), Boryslav−Pokuttya and Sambir (Stebnik). The Boryslav−Pokuttya Unit is the main oil reservoir in the Ukrainian Carpathians with multi- ayered oilfields, including the largest one – Boryslav. In this region ozokerite deposits are also known, hosted in the salt-bearing Lower Miocene Vorotyscha Beds. The city of Drohobych has become famous for its long tradition of salt trade. In the 19th century the period of rapid development started when the oil industry flourished in the vicinity, although the town was still in the shadow of Boryslav. The city of Truskavets, the famous health resort, has several mineral waters, also related to the oilfields, including the famous “Naftusia” spring. Another interesting site is Urych – the place where patients from the Truskavets resort travelled in order to admire scenic crags of the Yamna Sandstones and ruins of the Tustan Castle. The region of Boryslav and its surroundings was the site of the most effective petroleum exploitation in the territory of Poland in the past. This place is connected with the activity of Stanisław Szczepanowski (1846-1900), pioneer of oil industry and industrialization of the Galicia province.